Oil foams stabilized by POSS/organosilica particle assemblies: application for aerobic oxidation of aromatic alcohols. Issue 18 (6th April 2022) - Zhang, Shi; Dedovets, Dmytro; Pera-Titus, Marc
Abstract : Oil foams stabilized by a dual particle system combining surface-active catalytic organosilica particles and amphiphilic polyhedral oligomeric silsesquioxanes afford high catalytic activity in the aerobic oxidation of pure aromatic alcohols. Abstract : A novel amphiphilic polyhedral oligomeric silsesquioxane (POSS) with surfactant-like behavior was synthesized. By combining this new POSS, used as a frother, with surface-active catalytic organosilica particles, used as a stabilizer, we designed a dual particle system able to generate foams in pure organic solvents. Tunable foamability and foam stability were achieved in a variety of organic solvents by simply adjusting the POSS concentration. As a result, the catalytic activity was drastically boosted in the aerobic oxidation of pure aromatic alcohols under 1 bar O2 pressure. Particles were conveniently recycled with high foamability and the catalytic efficiency was maintained for at least 7 consecutive runs.